Effect of Different Endodontic Sealers on the Push-out Bond Strength of Fiber Posts - Frough Reyhani, Mohammad; Ghasemi, Negin; Rahimi, Saeed; Salem Milani, Amin; Omrani, Elnaz (Iranian Endodontic Journal, 2016)
Introduction: The aim of this in vitro study was to evaluate the effect of MTA-based sealer (MTA Fillapex), eugenol-based sealer (Dorifill) and an epoxy resin sealer (AH Plus) on the bond strength of fiber posts cemented with a self-etch adhesive. Materials and Methods: The root canals of 72 maxillary incisors were prepared using the step-back technique after removing/cutting off the crowns. The samples were randomly divided to 4 groups (n=18). In group 1 (the controls) gutta-percha was used without sealer. In groups 2, 3 and 4, the canals were filled with gutta-percha using AH Plus, Dorifill and MTA Fillapex sealers, respectively, by cold lateral compaction technique. After post space preparation, the fiber posts were cemented in the root canals using self-etch adhesive. Then 1-mm-thick disks were prepared from the coronal thirds of all the root canals and subjected to a push-out test. Data were analyzed using the one-way ANOVA and post hoc Tukey’s tests. Results: The maximum (4.45±0.09 MPa) and minimum (1.02±0.03 MPa) bond strength values were recorded in the control and Dorifill groups, respectively. The mean push-out bond strength values were similar for MTA Fillapex and AH Plus sealers (P>0.05). However these values were significantly higher than that of the Dorifill sealer (P<0.05). Conclusion: Sealer type affected the bond strength of the fiber posts and MTA Fillapex decreased the dislodgment resistant of the fiber post. Keywords: Bond strength; Resin Cement; Root Canal Sealer